Aggregate matching in Spain: Time series analysis using cointegration techniques - Ewa Gałecka-Burdziak (Contemporary Economics, 2016)
I analyze the matching process in the Spanish labor market from 1994-2005. I use monthly registered unemployment data and refer solely to public employment intermediation. This period reflects an upward movement along a downward sloping Beveridge curve; therefore, major changes in the process efficiency should not be observed. I narrow the considerations to a job queuing model, which is the most relevant description of the labor market matching process in Spain, according to the literature. I apply various quantitative methods to address the problem of non-stationary data. The Engle-Granger estimates emphasize the crucial role of the demand in generating the outflows from unemployment to employment. The ECT coefficient confirms that the model efficiently approaches the new equilibrium. These findings confirm that job seekers find themselves on the disadvantaged side of the market and compete for scarce job offers, which, in turn, are ascribed randomly to the workers. The diagnostic tests of the VAR models question the relevance of a multivariate space analysis because the outflow from unemployment to employment appears to be the sole endogenous variable.
Keywords: J63; J64; 330; labor market matching; job queuing model; time series analysis; Spanish labor market